La Détente Gréco-Turque et les Minorités - Akgönül, Samim (Études helléniques / Hellenic Studies, 2001)
The rights of the Greek-speaking minority in Turkey (3,000) and the Turkish-speaking Muslim minority in Western Thrace (120,000) have not always been respected. Both minorities have experienced legal and political problems, as well as cultural difficulties with the majority population which has either no knowledge or inaccurate perceptions of the minority. The current period of detente between Athens and Ankara must enable the minorities to improve their situation without forgetting the possibility of the opposite occurring due to potential bilateral friction.